ANALYSIS OF THE USE OF ANTIMICROBIAL AGENTS IN CESAREAN SECTION FOR ANTIBIOTIC PROPHYLAXIS AND THERAPY - Tashtanbekova Ch.B.; Evstratov A.A.; Titarenko A.F.; Aleksandrova E.G.; Ziganshina L.E. (Uzbekistan Open Conference, 2025)
This article presents the results of an assessment of the practice of prescribingantimicrobial agents for antibiotic prophylaxis and antibiotic therapy during cesarean section, and alsoanalyzes the pharmacoeconomic effectiveness of using antimicrobials in the prevention and treatment ofinfectious complications.
Keywords: Antibiotic prophylaxis; antibiotic therapy; cesarean section